The effect of selenium biological enhancement on cucumber growth and powdery mildew control under greenhouse conditions - Xiaodi Xu; Zhangbo Chen; Wenru Wang; Kai Pan (Scientific Reports)
Abstract In this study, we clarified the effects of selenium fertilizer application on the growth of cucumber, explored the impact of exogenous selenium on the control of powdery mildew and its pathogens. Selenium-enriched ionic fertilizer and cucumber were selected as the test materials. A one-way, randomized design was adopted to set up four selenium solutions with concentrations of 0 mg/L, 3 mg/L, 6 mg/L, and 12 mg/L to investigate the effects of biofortification with different amounts of selenium concentrations on the growth of cucumber and the occurrence of powdery mildew in greenhouses. A leaf inoculation test was conducted by setting up three groups of treatments: water and fungicide (seedling fungicide) as the control groups, and 6 mg/L selenium-enriched ionic fertilizer as the treatment group. These treatments were selected to investigate the effect of selenium on the control of powdery mildew in greenhouse-grown cucumbers as well as the effect of selenium on the germination of powdery mildew pathogen spores. The results demonstrated that both the 6 mg/L and 12 mg/L selenium-enriched ionic fertilizer solutions had growth-promoting and yield-increasing effects on cucumber and that the difference in the growth-promoting effects of these treatments was insignificant. The 3 mg/L, 6 mg/L, and 12 mg/L treatments improved the nutritional quality of cucumber fruits, reducing the total acidity of the fruits and increasing the content of soluble proteins in the fruits; the 6 mg/L and 12 mg/L treatments increased the content of selenium in the fruits, and the difference in selenium enrichment between the two treatments was not significant. The 6 mg/L selenium solution had the greatest effectiveness in alleviating leaf photosynthesis inhibition by the powdery mildew fungus, in mitigating powdery mildew damage and in reducing the plant disease index. The results of the leaf inoculation trials revealed that at a concentration of 6 mg/L, the effects of the selenium-enriched ionic fertilizer were comparable to those of pharmaceutical treatments for powdery mildew disease. The activities of superoxide dismutase and peroxidase in all treatments tended to increase but then decreased within 72 h after pathogen inoculation. Nevertheless, selenium fertilizer treatment inhibited the germination of powdery mildew pathogen conidia, the number of conidial germination shoot tubes and mycelium formation.